2021
DOI: 10.3390/ma14102642
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Performance of Steel Fibre Reinforced Concrete Exposed to Wet–Dry Cycles of Chlorides and Carbon Dioxide

Abstract: This paper presents an experimental study investigating the corrosion damage of carbon-steel fibre reinforced concrete (SFRC) exposed to wet–dry cycles of chlorides and carbon dioxide for two years, and its effects on the mechanical performance of the composite over time. The results presented showed a moderate corrosion damage at fibres crossing cracks, within an approximate depth of up to 40 mm inside the crack after two-years of exposure, for the most aggressive exposure conditions investigated. Corrosion d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 27 publications
(47 reference statements)
0
5
0
3
Order By: Relevance
“…As mentioned, this work focused on the influence of the aforementioned experimental variables on the reduction of the maximum load and the residual resistance after the degradation process in bending tests. In general, the authors relied on the standard EN 14651: 2007 for three-point bending tests (Marcos-Meson et al, 2021), as well as the standards EN 1015-3:1999, EN 413-2 : 2016and EN 14889-1: 2006 for the use of superplasticizer, the air content and the type of fiber to be used respectively in the preparation of concrete specimens (Marcos-Meson et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…As mentioned, this work focused on the influence of the aforementioned experimental variables on the reduction of the maximum load and the residual resistance after the degradation process in bending tests. In general, the authors relied on the standard EN 14651: 2007 for three-point bending tests (Marcos-Meson et al, 2021), as well as the standards EN 1015-3:1999, EN 413-2 : 2016and EN 14889-1: 2006 for the use of superplasticizer, the air content and the type of fiber to be used respectively in the preparation of concrete specimens (Marcos-Meson et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…, the fibers improve the tensile properties of concrete, fatigue resistance, impact resistance, and toughness and help control cracking (Behbahani & Nematollahi, 2011;Kaur et al, (2012), Ferreira et al, 2018Zhang et al, 2020). SFRC is used, for example, in tunnel lining, highway construction, and buildings prone to earthquake damage (Berrocal, 2015;Marcos-Meson et al, 2019;Zhang et al, 2020). In addition, the SFRC is applied in infrastructures with aggressive environments, such as industrial floors, buildings to store nuclear waste, and hydraulic and marine structures, such as docks, oil platforms, and gas pipelines (Doo-Yeol et al, 2021;Hou et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Исследования, посвященные оценке стойкости бетонов к различным видам агрессивных воздействий, представлены в работах [4][5][6][7][8][9][10]. Например, в работе [4] авторами была выполнена оценка коррозионной стойкости порошкового бетона, где по результатам экспериментов было установлено, что применение надсернокислого аммония в качестве агрессивного раствора позволит значительно ускорить процесс испытаний цементных композитов на сульфатостойкость.…”
Section: Introductionunclassified
“…Lu et al [26] studied the effect of the concrete mix ratio, dry-to-wet ratio, and exposure time on chloride ion penetration into concrete under the action of dry and wet cycles; the depth of chloride ion penetration increased with the increase in dry-and-wet-cycle air-drying time and exposure time. Xu et al [27] and Marcos-Meson et al [28] concluded that carbonation will accelerate the chloride ions transport in concrete under dry and wet cycles. Dong et al [29] investigated the chloride ion transport and service life of aeolian sand concrete under dry-wet cycles.…”
Section: Introductionmentioning
confidence: 99%